STRATEGI PENGEMBANGAN URBAN NIGHT TOURISM STUDY CASE: RAMINTEN CABARET SHOW JOGJAKARTA - Tirtadidjaja, Andari; Sarudin, Rendy (LPPM Institut Pendidikan Nusantara Global, 2023)
The Raminten Cabaret Show is an entertainment-based tourist attraction that presents the humorous behavior of actors and actresses who appear on stage where visitors can see various parodies of various famous figures. This makes The Raminten Cabaret Show one of the unique Night Life Tourism Attractions or Urban Night Tourism in the City of Jogjakarta and provides adding value ​​as City Branding to the City of Jogjakarta and can increase interest in visiting the city of Jogjakarta. This study uses a qualitative descriptive research method, namely by using primary data collection techniques through interviews with visitors to The Raminten Cabaret show and an in-depth literature study. The results of this study are strategies that can develop Urban Night Tourism in Jogjakarta by focusing on City Branding, Development of Tourist Attractions, and Increasing visits to the city of Jogjakarta. The Raminten Cabaret Show can be used as an alternative for tourism in Jogjakarta because it has a style that is different from other types of tourism and can make City Branding Jogjakarta stronger as a tourist city that has various tourist attractions and can increase interest in visiting the city of Jogjakarta.